Searching for the perfect goalkeeping personality. Myth or reality? - Spielmann, Jan; Otte, Fabian; Schumacher, Tom; Mayer, Jan; Klatt, Stefanie (Frontiers in Psychology, 2024)
Background Psychological factors such as personality characteristics are influential factors of the goalkeeping performance in football (soccer). Not only for individualized treatment in practice, also from a scientific point of view, profiling goalkeepers is a relevant part of understanding athletes. The aim of this study was to investigate personality traits of goalkeepers of different expertise, age, and sex. Methods Using the Five Factor Model of personality we assessed personality traits of 132 male and female football goalkeepers ranging from youth to senior and low to elite level. A series of analysis investigated differences between the groups focusing on expertise, age, and sex. Results Significant differences in the personality trait agreeableness between groups of different expertise and sex could be detected. Although a significant difference in neuroticism levels of males and females could be shown. Conclusion This study was a first step of profiling football goalkeepers of different expertise, age, and sex. The study calls for more replication in this specific field of football and goalkeeping in general to understand the influence of personality characteristics on sport performance.